2015
DOI: 10.1002/art.39274
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Enhancement of Patient Recruitment in Rheumatoid Arthritis Clinical Trials Using a Multi‐Biomarker Disease Activity Score as an Inclusion Criterion

Abstract: ObjectiveRheumatoid arthritis (RA) clinical trials often exclude patients who have low C‐reactive protein (CRP) levels, which slows enrollment into the trial. The purpose of this study was to determine whether high Multi‐Biomarker Disease Activity (MBDA) scores (>44) in RA patients with low CRP levels (≤10 mg/liter) could be used as a complement to CRP levels >10 mg/liter to enhance patient recruitment without affecting clinical trial outcomes.MethodsWe evaluated patients from the Swedish Pharmacotherapy (SWEF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Our search strategy identified an initial 718 studies, with 470 remaining after excluding duplicates (Figure ). Full‐text review of 121 studies was completed with exclusion of those reported only in abstract form (n = 98) or without original data (n = 1), resulting in 22 articles included in the systematic review . Eight studies showed correlations with RA disease activity measures and were included in the meta‐analyses .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our search strategy identified an initial 718 studies, with 470 remaining after excluding duplicates (Figure ). Full‐text review of 121 studies was completed with exclusion of those reported only in abstract form (n = 98) or without original data (n = 1), resulting in 22 articles included in the systematic review . Eight studies showed correlations with RA disease activity measures and were included in the meta‐analyses .…”
Section: Resultsmentioning
confidence: 99%
“…In a separate analysis from the SWEFOT trial, patients with high MBDA scores receiving triple therapy were more likely to have RP after 2 years of follow‐up than patients receiving MTX and infliximab . Additional outcomes reported on the MBDA included its potential to increase recruitment to clinical trials (i.e., identifying patients with low CRP who would otherwise be excluded) , as well as its ability to predict disease relapse .…”
Section: Resultsmentioning
confidence: 99%
“…If baseline measures or their early changes suggest possible treatment failure, an earlier change of treatment could be considered, potentially improving the clinical course and minimizing unnecessary healthcare utilization. In addition, elevated baseline MSUS and/or MBDA scores may provide value as inclusion criteria in randomized clinical trials allowing for a more homogenous group of RA patients with high disease activity and risk for joint damage [37].…”
Section: Discussionmentioning
confidence: 99%
“…The biomarkers in the MBDA test reflect the biology of RA and consist of cytokine-related proteins (IL-6, TNF-R1), acute phase reactants (CRP, serum amyloid A), an adhesion molecule (VCAM-1), growth factors (EGF, VEGF-A), matrix metalloproteinases (MMP-1, MMP-3), and adipokines (leptin, resistin). The MBDA score is an integer on a scale of 1 to 100, with disease activity categories of low (< 30), moderate (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) and high (> 44) [10]. Minimally clinically important difference (MCID) for MBDA score is ≥8 [23].…”
Section: Mbda Testingmentioning
confidence: 99%
“…We would encourage readers to make the distinction between the scientific validity of a diagnostic test and its clinical utility. There is already a sizable evidence base supporting the development and validation of the MBDA test in diverse RA patient cohorts (9)(10)(11)(12)(13)(18)(19)(20)(23)(24)(25). A prospective clinical trial is underway to rigorously evaluate its clinical utility and its potential role in RA patient management (26).…”
Section: To the Editormentioning
confidence: 99%